Ds Dirk van der Hoff se bydrae tot die ontwikkeling van die Christelik-nasionale onderwysstelsel in die ZAR - Oliver, E. (Hervormde teologiese studies, 1992)
Reverend Dirk van der Hoff's contribution to the development of Christian National Education in the Zuid-Afrikaansche Republiek Today, Afrikaners are closely associated with the Christian National system of education. This system has a long and interesting history and many people have been involved in its development. This article shows the vital and essential role that Reverend Dirk van der Hoff, the first resident minister of religion in the ZAR, played in the structuring of CNE.